Internal Variability Dominates Over Externally Forced Ocean Circulation Changes Seen Through CFCs. Issue 9 (9th May 2020) - Lester, J. G.; Lovenduski, N. S.; Graven, H. D.; Long, M. C.; Lindsay, K.
Abstract: Observations of oceanic transient tracers have indicated that the circulation in the Southern Ocean has changed in recent decades, potentially driven by changes in external climate forcing. Here, we use the CESM Large Ensemble to analyze changes in two oceanic tracers that are affected by ocean circulation: the partial pressure of chlorofluorocarbon‐12 (pCFC12) and the idealized model tracer Ideal Age (IAGE) over the 1991 to 2005 period. The small ensemble mean change in IAGE suggests that there has been very little externally forced change in Southern Ocean circulation over this period, in contrast to strong internal variability. Further, our analysis implies that real‐world observations of changes in pCFC12 may not be a robust way to characterize externally driven changes in Southern Ocean circulation because of the large internal variability in pCFC12 changes exhibited by the individual ensemble members. Plain Language Summary: It is important to understand how the circulation of the Southern Ocean responds to external factors, such as changing surface winds. Circulation changes are difficult to measure over such a large scale, but we can infer changes by looking at the spreading and mixing of tracers in the ocean. Recent studies using the tracer chlorofluorocarbon‐12 (CFC12) have found evidence that the Southern Ocean circulation changed from the 1990s to the 2000s. Our study uses a computer model which simulated the twentieth century oceanic uptake of CFC12, many times over, providing a statistical spread of the internal variability of the ocean. We compared the modeled CFC12 evolution to real‐world observations, along with a second model tracer called Ideal Age which we use to detect circulation changes. The model results suggest that the changes we observe in CFC12 from 1991 to 2005 are dominated by internal variability, or noise, rather than coherent circulation change, as measured by Ideal Age. The results indicate that human‐induced trends in ocean circulation in some regions will only be detectable over periods longer than one or two decades. Key Points: A model ensemble analysis indicates that externally forced ocean circulation changes from 1991 to 2005 are smaller than internal variability The changes in modeled CFC12 between 1991 and 2005 are subject to large internal variability Large internal variability in oceanic tracer changes challenges our ability to detect forced changes in circulation from these tracers